Risk Factors Associated with Work Accidents on Nurses in Dr. RM. Pratomo District General Hospital Bagan Siapiapi Rokan Hilir District - Wahyuni (LLDIKTI Wilayah 1, 2022)
The results of the 2016 National Safety Council report show that the Occurrence of work accidents in hospitals was 41% greater than another industrial workers. Based on the results of interviews conducted with 10 nurses in Dr. RM. Pratomo District General Hospital, 6 of them work accidents while the other 4 nurses did not experience work accidents. The purpose of this study was determine the risk factors associated with work accident on nurses in Dr. RM. Pratomo District General Hospital. The study used an analytical survey method with a cross sectional approach. The research population is all nurses as many as 124 people with a sample of 95 people were taken using accidental sampling technique. Data analysis used univariate, bivariate and multivariate analysis with logistic regression test statistics. The results showed that the p-value = 0.326, knowledge = 0.008, attitude = 0.241, action = 0.031, policy = 0.030 and use of PPE = 0.007. The conclusion of this study is that there is relationship between knowledge, actions, policy and the use of PPE with work accidents, While tenure and attitudes have no relationship with work accidents. It is hoped that this research can be used as input for hospital management, especially hospital leaders, heads of installations/sections on the importance of implementing work safety.